2014
DOI: 10.1111/hsc.12173
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of the implementation of the Interdisciplinary Management Tool: a reflective tool to enhance interdisciplinary teamwork using Structured, Facilitated Action Research for Implementation

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. Published versionNANCARROW, Susan, SMITH, Tony, ARISS, Steven and ENDERBY, Pamela M. (2015). Qualitative evaluation of the implementation of the interdisciplinary management tool: a reflective tool to enhance interdisciplinary teamwork using structured, facilitated action research for implementation. Health & Social Care In The Community, 23 (4), 437-448. Results: The IMT was implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…Part 3 consists of assessment instruments to measure team functioning at the staff and patient levels. Two studies [ 52 , 68 ] conducted on same sample Triad for Optimal Patient Safety (TOPS) Sehgal et al, 2008 [ 43 ] TOPS involves development of a 4-hour teamwork training program for staff on an inpatient unit combining didactics, facilitated discussion of a safety trigger video, and small-group exercises to enhance communication skills and team behaviors. Three studies [ 37 , 38 , 43 ] conducted on same sample Geriatric Interdisciplinary Team Training (GITT) Siegler, 1998 [ 66 ] The GITT initiative was launched by the John A. Hartford Foundation in 1995, and has continued to inform team-building interventions into the twenty-first century.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part 3 consists of assessment instruments to measure team functioning at the staff and patient levels. Two studies [ 52 , 68 ] conducted on same sample Triad for Optimal Patient Safety (TOPS) Sehgal et al, 2008 [ 43 ] TOPS involves development of a 4-hour teamwork training program for staff on an inpatient unit combining didactics, facilitated discussion of a safety trigger video, and small-group exercises to enhance communication skills and team behaviors. Three studies [ 37 , 38 , 43 ] conducted on same sample Geriatric Interdisciplinary Team Training (GITT) Siegler, 1998 [ 66 ] The GITT initiative was launched by the John A. Hartford Foundation in 1995, and has continued to inform team-building interventions into the twenty-first century.…”
Section: Resultsmentioning
confidence: 99%
“…clear objectives, evaluating success in meeting practice objectives, meeting attendance, communication) ELDER Lange et al, 2011 [ 42 ] Trainee Evaluations: Generally positive but not subjected to empirical testing Mager et al, 2012 [ 36 ] Trainee Evaluations: 97–100% of staff at each site rated the training positively Teamwork Attitudes/Knowledge: Notes and checklists indicated good communication, respect, and collaboration during the simulations themselves (although not subjected to pre-post analysis) Mager and Lange, 2014 [ 49 ] Trainee Evaluations: Qualitatively, participants reported preferring innovative teaching methods (e.g. case-based discussion) over traditional lecture Teamwork Attitudes/Knowledge: Participants did not show statistically significant improvement in knowledge of team concepts (based on a GITT instrument) or scores on an Interdisciplinary Teamwork IQ assessment GITT Clark et al, 2002 [ 56 ] Team Functioning: No statistically significant changes for domains such as communication and cohesion (based on a team function assessment scale) IMT Nancarrow et al, 2012 [ 52 ] Trainee Evaluations: Generally positive, but some participants expressed concerns about the amount of time required to attend workshops and complete associated assessments Team Functioning: Workforce Dynamics Questionnaire [ 51 ] suggested improved team working score improved over time ( p- value significant but not reported); no statistically significant change in several other teamwork domains; qualitative assessment ( n = 15) suggested overall improved teamwork Patient Impact: Changes in patient satisfaction pre- to post- intervention significant at some but not all sites Nancarrow et al, 2015 [ 68 ] Trainee Evaluations: This study expands on the findings from the trainee evaluations and qualitative findings reported in the Nancarrow et al [ 52 ] (with results being generally but not universally positive) Rehabilitation Team Training (no formal name provided) Stevens et al, 2007 [ 70 ] Trainee Evaluations: 100% of attendees agreed or strongly agreed that workshop met goals of emphasizing team functioning and its impact on patient outcomes; attendees less enthusiastic about written information summarizing survey responses related to team functioning Strasser et al, 2008 [ 45 ] Patient Impact: More patients treated by intervention teams gained above the ...…”
Section: Resultsmentioning
confidence: 99%
“…The NIH Field Guide on Collaboration and Team Science, 7 originally published by the National Cancer Institute in 2010 and updated in 2018, provides resources and tools for effective team operation. Other tools designed to enhance team effectiveness 8,9 and training curricula 10,11,12 have also been developed and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The Association of American Medical Colleges (AAMC) requires participation as a member of an interprofessional team as an Entrustable Professional Activity (EPA) [7]; while the American Association of Colleges of Nursing (AACN) places a strategic focus on IPE to improve innovation within the discipline and within the field of healthcare [8]. Innovations are stimulated by diverse perspectives, academic backgrounds, and require strong skills in teamwork, leadership, and communication [9,10]. When students collaborate with others outside their area of expertise, creative thinking skills are enhanced as well as the students’ ability to generate solutions through teamwork [11].…”
Section: Introductionmentioning
confidence: 99%